PENGEMBANGAN PEMBALUT BUNGA TELANG BERBASIS NANOTECHNOLOGY DAN AKURASI DALAM DETEKSI DINI KETUBAN PECAH DINI - Miraningtyas, Ating; Wijayanti, Krisdiana; Isnawati, Muflihah (Poltekkes Kemenkes Bandung, 2024)
The incidence of premature rupture of membranes (PROM) reaches 12.3% of total births throughout the world. Efforts to detect early KPD still face problems, namely the use of litmus paper which is small in size and there are no regulations regarding its use, so a tool is needed that has the same function as litmus paper in detecting amniotic fluid which can be used and used by pregnant women independently. The study aimed to develop nanotechnology-based butterfly pea flower pads in early detection of PROM. The research method used is Quasy Experimental, with purposive sampling technique, using an observation sheet. The sanitary napkin design is designed with a telang flower indicator for PROM detection with a sanitary napkin length of 22 cm and a width of 7 cm. Testing was carried out on 30 pregnant women in Jati District, Blora Regency, at January 20 to February 19, 2024. Statistical analysis uses Anova, Multiple Comparison test and Tukey's Difference Test. The research results obtained accuracy, sensitivity and specificity values ​​of 100%. Sanitary napkins do not cause irritation to the skin, have an ideal absorbency of 10x the initial weight, a chlorine concentration of 1.8 ppm with a total of 39 bacterial colonies which is still below the quality threshold for sanitary napkins. The study concluded that butterfly pea flower sanitary napkin products can accurately replace litmus paper as an indicator for early detection of PROM.